BBS News Vol.7(1) (Bangladesh Journal of Bioethics, 2016)
BBS signed a MOU in January 2015 with AUSN, Arizona, USA for sending its members with scholarships for one year Master of Bioethics & Global Public Health (MBGPH) and Master of Public Health (MPH). Out of 15 students, eleven students have graduated for the session of 2014-2015.